Medical students' biomedical and clinical knowledge: Combining longitudinal design, eye tracking and comparison with residents' performance. (December 2017) - Södervik, Ilona; Vilppu, Henna; Österholm, Erika; Mikkilä-Erdmann, Mirjamaija
Abstract: This study combines longitudinal and individual process-level analyses to investigate medical students' biomedical knowledge and how they generate a diagnosis for a patient case text. The diagnostic processes were investigated using the eye-tracking method, and students' processes were compared with those of residents. The results showed that students differed in their diagnostic performance in the beginning of the clinical phase. Of the students who had biomedical misconceptions in the preclinical phase, 69% ended up with an incorrect diagnosis, while 60% of students with accurate biomedical knowledge made a correct diagnosis. The processing of a patient case text was faster among better-achieving students and residents. Furthermore, residents' illness-script activation could be seen from their eye-movement data as a relatively longer reading time regarding the sentence that concerned the enabling condition of the case. Based on the results of the study, pedagogical suggestions are discussed. Highlights: Differences in biomedical and clinical knowledge among medical students are evident. 69% of those with biomedical misconceptions made an inaccurate diagnosis. Those who diagnosed the patient case correctly processed the text faster. Students and residents made different use of enabling conditions for the case. The eye-tracking method may enable the detection of the illness-script activation.